Measuring pollutant exposure using large-eddy simulation and virtual walkers: Analysis of tracer age statistics of idealised urban boundary-layer flows. (June 2023) - Duan, G.; Takemi, T.; Ngan, K.
Abstract: Pollutant exposure in the urban air quality literature has been typically interpreted from data for fixed locations, which provides an incomplete picture of exposure for pedestrians (or moving receptors). The current study proposes a simple model to parameterise the exposure time for a virtual walker to cross a pollutant cloud during its sweeping downstream across the avenue. The parameterisation, which depends on the centre-of-mass translation and the cloud size, shows satisfactory performance in areas away from the outlet, whence a substantial portion of the pollutants is removed from the control domain and a well-defined centre of mass geometrically vanishes. Applying the tracer age diagnostics, the occurrence time of first exposure for the moving receptors is quantified with no particular caution required for the outlet region. The mean tracer age recorded by the virtual walkers is shown to be up to 25 %– 75 % smaller than conventional spatial averages, implying earlier exposure to the pollutants and hence a reference timescale relying on the latter may lead to delayed emergency response. Evacuation route prioritisation based on virtual walker measurements coincides with that indicated by the parameterisation, suggesting the potential usefulness of the model for exposure risk evaluation against atmospheric air pollution incidents. Highlights: Pollutant cloud size and centre-of-mass translation downwind affect exposure. A simple parameterisation is proposed for exposure time quantification. Occurrence time of first exposure is quantified using the mean tracer age. Virtual walkers show earlier exposure than estimates by fixed receptors.